Checklist of Cycloposthiidae species (Ciliophora, Entodiniomorphida), with a brief review on taxonomy, morphology and hosts - Fregulia, Priscila; Cedrola, Franciane; Dias, Roberto Júnio Pedroso; D’agosto, Marta (Zootaxa, 2020)
The family Cycloposthiidae include 69 species, distributed in 17 genera, all of them described in symbiotic association with various mammalian host species. The taxonomic classification of the family is confused because of its broad diagnosis and absence of synapomorphies. To validate taxa and eliminate synonyms, the present work performed a brief taxonomic review of Cycloposthiidae, compiling morphological characterization, host records, and geographic location data. According to our review, the family should be instead, composed of 13 genera and 66 species; it was observed that the currently in use taxonomic characters do not reflect evolutionary divergence; and that the broad host range of Cycloposthiidae may be linked to cortex characteristics of these organisms or because of the fact that they do not constitute a monophyletic group. Thus, the performance of more molecular phylogenetic studies, including more cycloposthiid representatives and as well as the use of recent morphological techniques would be necessary to clarify the taxonomy of the group.